Guido d'Arezzos's "Regular Rithmice", "Prologus in Antiphonarium" and "Epistola ad Michahelem" a critical text and translation - Caldwell, John 1938- (Oxford University Press, Oxford, 2000)
RESUMEN: Autora Dolores Pesce. "Musicological Studies", lxxiii. The Institute of Medieval Music, Ottawa, 1999.